Analysis of fortuitous matches in a STR genotype database from Mexico and its forensic efficiency parameters - Joaquín Alejandro Quiroz-Mercado; Ricardo Jesus Ríos-Rivas; Víctor Manuel Martínez-Sevilla; Gabriela Chávez-Marín; Hueman Jaimes-Díaz; Juan Carlos Santiago-Hernández; Rogelio Maldonado-Rodríguez; Héctor Rangel-Villalobos (Egyptian Journal of Forensic Sciences, 2017)
Abstract Background Commercial kits for Human Identification (HID) purposes, based on 15 short tandem repeat (STR) regions, allow the resolution of most forensic and paternity cases. However, some pitfalls arise in situations such as identification of missing persons, disaster victims, and in motherless paternities. We describe nine fortuitous matches found during the inclusion of new DNA profiles and/or searching for missing persons within a Mexican STR database (N = 2000). For these cases, we estimated both the likelihood ratio (LR) and the modified LR according to National Research Council (NRC) recommendations (i.e., LRNRC). Results In most cases, low LRNRC values (~1 or <1) and elevated presence of modal STR alleles (>50% loci) were indicative of fortuitous matches. We estimated a significant increase in the observed frequency of fortuitous matches in this database when using the PowerPlex 16 DNA-typing system. In addition, forensic efficiency parameters for this HID kit are reported for the State of Mexico based on a population sample selected from the STR database (n = 493). We describe the population structure and relationships, which detail comparative homogeneity among Mexican-Mestizos from the Central region, excluding the Western region. Conclusions The results suggest that additional / more powerful HID systems should be used when searching for relatives within STR databases in order to enable definitive conclusions, which are also required in cases of motherless paternity and massive disasters. The genetic structure described herein allows forensic geneticists to use alternative STR population data during statistical interpretation, given that most Mexican populations do not have their own STR databases.